Inventarisasi Jenis Tumbuhan Paku di Hutan Watumbolo, Kabupaten Sumba Barat Daya - Andriani Rafael; Yanti Daud; Octaviani Hungu (Jurnal Ilmu Pertanian Indonesia, 2023)
Indonesia is a tropical country that has high plant biodiversity. One of the plant groups that are rich in species are ferns. Ferns still exist until now and estimated at 10.000 species, which 3.000 species are grown out in Indonesia. Watumbolo forest is located in South West Sumba, with the average temperature ranges from 21-34°C, therefore the varians types of plants grow well in this forest, including ferns. The aim of this study was to identify the types of ferns found in the Watumbolo forest. Observations were also made on environmental conditions which included: air temperature, light intensity, soil moisture, and soil pH. This research was conducted using descriptive exploration method. The results obtained 18 species of ferns, namely: Asplenium nidus, Gleichenia linearis, Blechnum orientale, Davallia denticulata, Nephrolepis biserrata, Drynaria quercifolia, Drymoglossum piloselloides, Drynaria parishii, Nephrolepis hirsutula, Angiopteris evecta, Cyclosorus interruptus, Christella subpubescens, Lygodium microphyllum, Lygodium palmatum, Schizaea digitata, Selaginella plana, Lycopodium cernuum, and Psilotum nudum. Therefore, the results of temperature measurements in Watumbolo forest were between 22-28°C, air humidity 56-70%, light intensity 1069lux-6116lux, soil pH 7, and soil moisture 70-72%. Keywords: ferns, South West Sumba, Watumbolo Forest